2009
DOI: 10.1890/08-0792.1
|View full text |Cite
|
Sign up to set email alerts
|

Is the growth of temperate forest trees enhanced along an ambient nitrogen deposition gradient?

Abstract: Abstract. The extent to which atmospheric N deposition is enhancing primary production and CO 2 sequestration along the ambient N deposition gradients found within many regional temperate forest ecosystems remains unknown. We used tree diameter measurements from 1984 and 2004, allometric equations, and estimates of wet N deposition from 32 permanent plots located along an ambient N deposition gradient in the Adirondack Park, New York, USA, to determine the effects of N deposition on the basal area and woody bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 43 publications
(52 reference statements)
1
29
0
1
Order By: Relevance
“…Although a number of studies have reported a general positive effect of N enrichment on plants in N-limited forests and a negative effect of excess N (e.g. Aber et al, 1998;Högberg et al, 2006;Gilliam, 2006;Thomas et al, 2010), specific responses of plants appeared to be highly growth form-dependent and ecosystem-dependent (LeBauer and Treseder, 2008;Bedison and McNeil, 2009;Dirnböck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies have reported a general positive effect of N enrichment on plants in N-limited forests and a negative effect of excess N (e.g. Aber et al, 1998;Högberg et al, 2006;Gilliam, 2006;Thomas et al, 2010), specific responses of plants appeared to be highly growth form-dependent and ecosystem-dependent (LeBauer and Treseder, 2008;Bedison and McNeil, 2009;Dirnböck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several sources indicate that red maple growth and survival increases with increasing N deposition. Thomas et al (2010) found increased growth and survival with increased deposition from 3 to 11 kg N ha -1 yr -1 , while Bedison and McNeil (2009) . In West Virginia, red maple basal area increased with deposition from 12 to 14 kg N ha -1 yr -1 (Elias 2008).…”
Section: Species Range and Critical Loadmentioning
confidence: 99%
“…2%, 但由于细根周转快速, 消耗了20%−30%的年净 初级生产力 (Jackson et al, 1997;Poorter et al, 2011), (Eissenstat et al, 2000), 这 在氮沉降梯度研究和元素添加试验中得到了广泛证 明 (Ostonen et al, 2007;Li et al, 2015)。 近几十年来, 由于工农业发展和化石燃料的大 量燃烧导致氮沉降在全球范围增加, 人类活动极大 地干扰了全球氮循环 (Galloway & Cowling, 2002;Galloway et al, 2004), 对森林生态系统物质循环造 成了潜在的巨大影响(吕超群等, 2007)。大量研究表 明, 日益增加的氮沉降会增加土壤氮素可利用性, 多数情况会下提高植被地上部分生产力 (Bedison & Mcneil, 2009)。然而森林植物根系对土壤氮素增加 的响应方向和程度却存在很大的不确定性。有研究 表明氮添加增加了根系寿命, 减缓了细根周转速率 (Jourdan et al, 2008;于水强等, 2009;Mei et al, 2010), 但也有研究观察到与之相反的结果 (Johnson et al, 2000;Wang et al 2012 …”
Section: 细根占陆地生态系统植物总生物量的比例小于unclassified